Am Rande des Grabs Todeskonzepte und Bestattungsritual in der frühmittelalterlichen Alamannia - Hausmair, Barbara (Sidestone Press, 2015)
The original circumstances in which archaeological remains came into being are crucial for the interpretation of the material record. Burials are first and foremost a result of a very traumatic event in a society - the death of one of its members. It is due to this context that burials represent a primary source for understanding past societies' attitudes towards death. Barbara Hausmair traces death concepts and their influence on mortuary rituals in early medieval communities in what is today known as southwest Germany. Using the cemeteries of Bad Mingolsheim, Horb-Altheim and Weingarten as case studies, the author compares archaeological patterns based on grave goods and grave arrangements with anthropological data on age, sex, pathologies, trauma and migration patterns of the deceased. By connecting the observed patterns with social theories on human death behaviour, Hausmair dissects the complex network of the burial communities' social structures, death concepts and the newly constructed identities of the dead in the afterlife. Her thanatological approach provides original insights into the relationships between burial practices and ideas about death in Merovingian-period Alamannia by sensibly combining theoretical considerations with a thorough analysis of archaeological material.